2022
DOI: 10.3390/pharmaceutics14050938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fixed Oil on Ostwald Ripening of Anti-Oral Cancer Nanoemulsions Loaded with Amomum kravanh Essential Oil

Abstract: Recently, essential oil from Amomum kravanh (AMO) was reported to exert anti-oral cancer effects. Although it was more effective after being loaded into nanoemulsions, AMO without an Ostwald ripening inhibitor was unable to form stable nanoemulsions because of the Ostwald ripening phenomenon. In this study, we examined the influence of Ostwald ripening inhibitors, such as fixed oils and polyethylene glycol 4000 (PEG 4000), on nanoemulsion properties prepared by a phase inversion temperature method. Several fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Nanoemulsions prepared from GLO:VCO of 50:50 to 70:30 presented a small droplet size of approximately 50 nm, whereas the other GLO:VCO ratios resulted in a larger droplet size (80-150 nm). These results were consistent with those of previous studies reporting that the droplet size of essential oil nanoemulsion depends on the oil phase composition, especially the ratio of the essential oil to fixed oil [21,22]. After the temperature-cycling test, the droplet size of the GLO:VCO, at ratios ranging from 50:50 to 80:20, was not significantly different from the initial measurements, whereas 90:10-100:0 tended to increase after storage.…”
Section: Droplet Size and Zeta Potential Of Glo Nanoemulsionssupporting
confidence: 92%
See 1 more Smart Citation
“…Nanoemulsions prepared from GLO:VCO of 50:50 to 70:30 presented a small droplet size of approximately 50 nm, whereas the other GLO:VCO ratios resulted in a larger droplet size (80-150 nm). These results were consistent with those of previous studies reporting that the droplet size of essential oil nanoemulsion depends on the oil phase composition, especially the ratio of the essential oil to fixed oil [21,22]. After the temperature-cycling test, the droplet size of the GLO:VCO, at ratios ranging from 50:50 to 80:20, was not significantly different from the initial measurements, whereas 90:10-100:0 tended to increase after storage.…”
Section: Droplet Size and Zeta Potential Of Glo Nanoemulsionssupporting
confidence: 92%
“…As reported in previous studies, essential oils without fixed oil incorporation were unable to generate nanoemulsions with a droplet size in the nano range. Fixed oil was necessary to prevent Ostwald ripening during emulsion formation [21,22]. To achieve the smallest droplet size, the ratio of GLO to VCO in the range of 50:50 to 100:0 was analyzed before ODF fabrication.…”
Section: Preparation Of Nanoemulsionsmentioning
confidence: 99%
“…Similar results were obtained for cinnamon EO on normal rat fibroblasts (cell line F2408), where nontoxic concentration was approximatively 10 μg/ml, while the higher ones were cytotoxic ( Unlu et al, 2010 ). A higher level of EM induced cytotoxicity could be due to the small size of particles and their easier passage into the cells ( Weerapol et al, 2022 ). Although both EO and EM showed a cytotoxic effect, that does not exclude them from further research which should be performed to minimize cytotoxicity and enable their possible use.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have used fixed oils as Ostwald ripening inhibitors, including corn oil, 11 peanut oil, 12 and virgin coconut oil. 13 In our previous study, the impact of different fixed oils, including virgin coconut oil, palm oil, olive oil, soybean oil, and perilla oil, on the formation and stability of SMO nano- emulsions was investigated. Interestingly, it was found that the presence of 20% fixed oil, particularly perilla oil, led to the rearrangement of different molecules, bringing them into close proximity (within 5 Å).…”
Section: ■ Introductionmentioning
confidence: 99%
“…These triglycerides not only improve stability but also promote the formation of nanoemulsions with small droplet sizes when prepared using the phase inversion temperature method. Several previous studies have used fixed oils as Ostwald ripening inhibitors, including corn oil, peanut oil, and virgin coconut oil …”
Section: Introductionmentioning
confidence: 99%